Laryngeal distribution of recurrent respiratory papillomatosis in a previously untreated cohort. (17th July 2017) - Benedict, Peter A.; Ruiz, Ryan; Yoo, MiJin; Verma, Avanti; Ahmed, Omar H.; Wang, Binhuan; Dion, Gregory R.; Voigt, Andrew; Merati, Albert; Rosen, Clark A.; Amin, Milan R.; Branski, Ryan C.
Abstract : Objectives/Hypothesis: To describe the distribution of recurrent respiratory papillomatosis (RRP) lesions across 21 laryngeal anatomic regions in previously untreated patients at initial presentation to provide insight regarding the natural history of RRP. Study Design: Multi‐institutional, retrospective case series. Methods: Initial laryngoscopic examination videos of 83 previously untreated patients with adult‐onset RRP were reviewed. Papilloma locations were recorded using a 21‐region laryngeal schematic. Multivariate analyses by anatomic subsite were conducted for the entire population and for subgroups stratified by sex, age, and proton pump inhibitor (PPI) usage. Heat maps were generated, hierarchically color coding the anatomic distribution of disease. Results: In this cohort, RRP was most likely to occur on the true vocal folds (TVFs) and anterior commissure ( P < .0001, odds ratio [OR]: 7.02); within the TVFs, the membranous vocal folds (MVFs) were most likely to be affected ( P < .0001, OR: 3.56). The cohort was predominantly male (80.7%); males had a higher average number of affected sites ( P = .005) and were more likely to have lesions in any laryngeal subsite ( P < .0001, OR: 2.88, ) compared to females. PPI users were more likely than nonusers to have disease in any laryngeal subsite ( P = .0037, OR: 1.62), particularly in the posterior and subglottic regions ( P = .0061, OR: 2.53). Age was not correlated with lesion prevalence or distribution. Conclusions: In untreated patients presenting to three laryngology clinics, the MVFs were most likely to be affected by RRP. Males had more anatomic sites affected by papilloma than females. The influence of PPI use on RRP distribution warrants further investigation. Level of Evidence: 4. Laryngoscope, 128:138–143, 2018